Environmental and anthropogenic drivers of soil methane fluxes in forests: Global patterns and among‐biomes differences. (21st September 2020) - Gatica, Gabriel; Fernández, María E.; Juliarena, Maria P.; Gyenge, Javier
Abstract: Forest soils are the most important terrestrial sink of atmospheric methane (CH4 ). Climatic, soil and anthropogenic drivers affect CH4 fluxes, but it is poorly known the relative weight of each driver and whether all drivers have similar effects across forest biomes. We compiled a database of 478 in situ estimations of CH4 fluxes in forest soils from 191 peer‐reviewed studies. All forest biomes (boreal, temperate, tropical and subtropical) but savannahs act on average as CH4 sinks, which presented positive fluxes in 65% of the sites. Mixed effects models showed that combined climatic and edaphic variables had the best support, but anthropogenic factors did not have a significant effect on CH4 fluxes at global scale. This model explained only 19% of the variance in soil CH4 flux which decreased with declines in precipitation and increases in temperature, and with increases in soil organic carbon, bulk density and soil acidification. The effects of these drivers were inconsistent across biomes, increasing the model explanation of observed variance to 34% when the drivers have a different slope for each biome. Despite this limited explanatory value which could be related to the use of soil variables calculated at coarse scale ( 1 km), our study shows that soil CH4 fluxes in forests are determined by different environmental variables in different biomes. The most sensitive system to all studied drivers were the temperate forests, while boreal forests were insensitive to climatic variables, but highly sensitive to edaphic factors. Subtropical forests and savannahs responded similarly to climatic variables, but differed in their response to soil factors. Our results suggest that the increase in temperature predicted in the framework of climate change would promote CH4 emission (or reduce CH4 sink) in subtropical and savannah forests, have no influence in boreal and temperate forests and promote uptake in tropical forests. Abstract : We explored the combined influence of climatic, soil and anthropogenic drivers on soil CH4 fluxes in forests at global and biome scale using 478 in situ estimations from 191 peer reviewed studies. We found that combined climate and soil variables, but not anthropogenic drivers, explain spatial variations of soil CH4 fluxes in forests worldwide. In general, climatic drivers were more important than soil drivers at global scale. Interestingly, to different biomes, the main climatic and soil variables that determine the magnitude and direction of soil CH4 fluxes are not the same.